The Effect Of Service-Driven Market Orientation On Service Innovation: Literature Review And New Research Framework - Ratny, Seng; Arshad, Arif Mohammad; Gaoliang, Tian (Journal of Applied Business Research, 2017)
The aim of this paper is to analyse the literature regarding the association between service-driven market orientation and innovation in service organizations as well as create conceptual framework about this relationship. Scholars have suggested that the service firms implementing service-driven market orientation can perform significantly better than traditional market-orientation and become increasingly aware of market demands better than their competitors. The service firms need to react quickly and effectively to changing customers’ demands. Bring in the service-driven market orientation model for service sector leads to critical advantages and particularly their benefits on service innovation. The recent work examined the market orientation-innovation relationship regarding the service industries. An examination regarding the market orientation in service organization is presented along with the conceptual framework and conceptual model is recommended.
Keywords: Service-Driven Market Orientation; Service Innovation; Learning Orientation; Customer Orientation; Competitor Orientation